(3GdGJUGd h GdJShjb Hjf GdfXQjI h GdJWHjb (B/s - (3GdfhGYQI, CMeOs ((3YeGf(B: s (3OGQ GSGeI(B, s, 2009)
(3eGgjI GdGJUGd , ebheGJ h eYhbGJ GdGJUGd GdaYGd , GdGJUGdGJ GdGOGQjI , OhQ hSGFd GdGJUGd aj GdYdGbGJ GdYGeI , eGgjI GdJShjb h GdhXGFa GdJShjbjI , fXQI GdHY , GdTQGA h fXQI GdJShjb , GdeYdheGJ GdJShjbjI h HMhK GdJShjb , JLRFI GdShb , egGQGJ GdGJUGdGJ GdJShjbjI GdeejRI , JNWjW GSJQGJjLjGJ GdeRjL GdGJUGdj GdJShjbj , hSGFd h YfGUQ GdGJUGdGJ GdJShjbjI , aGYdjI GdGJUGdGJ GdJShjbjI , eaGgje GdGJUGdGJ GdJShjbjI GdeejRI , GdGJUGd GdGdcJQhfj aj GdJLGQI h GdJShjb (B.s
(3eQGLY U(B.311 ((3EbJfjJ SfI (B2010 (3H(B:10 (3fSN(B) (2014 -03 (3fSN(B)s
Keywords: (3GdGJUGds; (3GdGJUGd GdLeGgjQjs; (3GdEJUGdGJ GdEOGQjIs; (3GdJShjbs